2006
DOI: 10.1007/s10573-006-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical processes in the HNF flame

Abstract: Results of modeling the HNF flame structure are presented. From an analysis of literature data on the thermal decomposition and combustion of HNF, it is concluded that the dissociative vaporization of HNF proceeds via the route HNF liq → (N 2 H 4 ) g + (HC(NO 2 ) 3 ) g . The flame structure is modeled using a detailed kinetic mechanism consisting of 47 species and 283 elementary reactions. Its constituents are the decomposition mechanisms of hydrazine (N 2 H 4 ) g and trinitromethane (HC(NO 2 ) 3 ) g (nitrofor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It is commonly accepted ,,,, that the C−N bond dissociation is the primary reaction of the thermal decomposition of nitromethanes. Therefore, we also calculated the enthalpy of dissociation of the nitromethanes and the enthalpy of formation of the radical products (by atomization approach) using the spin-unrestricted versions of the above-mentioned methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is commonly accepted ,,,, that the C−N bond dissociation is the primary reaction of the thermal decomposition of nitromethanes. Therefore, we also calculated the enthalpy of dissociation of the nitromethanes and the enthalpy of formation of the radical products (by atomization approach) using the spin-unrestricted versions of the above-mentioned methods.…”
Section: Resultsmentioning
confidence: 99%
“…Trinitromethane (nitroform, 7 ) appears as the intermediate in the hydrazine nitroformate decomposition, which is a promising chlorine-free oxidant for the solid rocket fuel. Thermodynamic characteristics of nitroform and intermediates of its decomposition as well as the rate constants of elementary reactions are crucial for modeling the complex process of the hydrazine nitroformate combustion. , …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in the Introduction, the formation of nitroform ( 1 ) and hydrazine ( 3 ) in the gas phase upon thermolysis of HNF was usually attributed to the dissociative vaporization of HNF. ,,,, This means that the ionic structure, [C(NO 2 ) 3 ] − [N 2 H 5 ] + , was hypothesized not to exist in the gas phase. Note that the previous theoretical studies on the ADN and HNO 3 −NH 3 15 systems demonstrated that only hydrogen-bonded acid−base complexes could be localized on the potential energy surfaces of these systems.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the strong dependence of the HNF decomposition rate on the vessel innage (m/V) has been observed . This fact was proposed to be the evidence of the dissociative vaporization of HNF (Scheme ) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation